2011
DOI: 10.1128/mcb.05629-11
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of Mitochondrial Phosphatase Ptpmt1 in Embryogenesis Reveals a Mitochondrial Metabolic Stress-Induced Differentiation Checkpoint in Embryonic Stem Cells

Abstract: Mitochondria are involved in a number of cellular processes and are essential for both life and death. As the site of oxidative phosphorylation, these double-membrane organelles provide a highly efficient route for eukaryotic cells to generate ATP from energy-rich molecules. During the mitochondrial energy production process, reactive oxygen species (ROS), such as superoxide (O 2 Ϫ ) and hydrogen peroxide (H 2 O 2 ), are produced as by-products. In fact, mitochondria are the primary source of a majority of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 45 publications
0
58
0
Order By: Relevance
“…The recombinant protein exhibited phosphatase activity against PtdIns(5)P, but no other phosphoinositide ( 80 ). However, other reports have demonstrated that PTPMT1 can dephosphorylate PtdIns(3,5)P 2 , PtdIns(3,4)P 2 , and PtdIns(5) P in vitro ( 81 ). Furthermore, PtdIns(5)P is not dephosphorylated in vivo by this enzyme ( 82 ), but rather phosphatidylglycerolphosphate is the physiological substrate ( 82,83 ); this is a lipid structurally very similar to PtdIns(5)P ( 84 ).…”
Section: Pten and Tpip Proteinsmentioning
confidence: 96%
“…The recombinant protein exhibited phosphatase activity against PtdIns(5)P, but no other phosphoinositide ( 80 ). However, other reports have demonstrated that PTPMT1 can dephosphorylate PtdIns(3,5)P 2 , PtdIns(3,4)P 2 , and PtdIns(5) P in vitro ( 81 ). Furthermore, PtdIns(5)P is not dephosphorylated in vivo by this enzyme ( 82 ), but rather phosphatidylglycerolphosphate is the physiological substrate ( 82,83 ); this is a lipid structurally very similar to PtdIns(5)P ( 84 ).…”
Section: Pten and Tpip Proteinsmentioning
confidence: 96%
“…Ectopic expression of UCP2 in human ESCs reduces glucose oxidation, impairs EB formation, and hampers early differentiation (32). Importantly, the mitochondrial metabolic stress-activated checkpoint in the control of ESC differentiation has been attributed to Ptpmt1 (proteintyrosine phosphatase, mitochondrial 1), a mitochondrial PTEN-like phosphatidylinositol phosphate phosphatase (29); enhanced aerobic glycolysis, decreased oxygen consumption, compromised mitochondrial fusion/dynamics, and blocked differentiation was observed in Ptpmt1 knock-out ESCs (29). This implicates mitochondria as the key player in ESC differentiation and metabolic reprogramming, which may represent a unique way to modulate the fate of ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Extinction difference between E1 and E2 was then used to calculate lactate concentration. The relative percentage of glucose metabolized to lactate was utilized for the assessment of glycolytic activity ( ATP Measurement-The total ATP content of ESCs was determined by using an adenosine 5Ј-triphosphate bioluminescent somatic cell assay kit (Sigma) as described elsewhere (29).…”
Section: ⌬/ϫmentioning
confidence: 99%
“…These results suggest that CBR activation induces a G 2 /M-phase cell cycle delay in HeLa cells. We consider that this might ultimately induce inhibition of cell proliferation, since there is evidence that cell cycle delay correlates with anti-proliferation [28,29].…”
Section: Cannabinoids Cause Cells To Delay In the G 2 /M Phase Of Thementioning
confidence: 99%